Use of Means of Ukrainian Folk Pedagogy in Formation of Moral and Ethical Concepts in Extracurricular Educational Work - Mariia Kopchuk-Kashetska (Vasyl Stefanyk Precarpathian National University, 2021)
The article identifies the peculiarities of the formation of moral and ethical concepts of students in extracurricular activities. In particular, positive influence of means of Ukrainian folk pedagogy on the education of moral qualities of students is revealed. Folk-pedagogical methods of stimulation, encouragement, motivation of children, and correction of their behavior are outlined. The process of formation and development of desirable moral qualities in children takes place in a close relationship between learning and education, as it is impossible, in the educational process to aim at the formation of some moral and ethical values, and in extracurricular educational work - others. The effectiveness of the process of moral and ethical education of children largely depends on the purpose and those educational tasks set by the teacher (educator), pedagogical tools and forms of organization of the pedagogical process, the principles of systematic and pedagogical cooperation of school and family in solving this problem. It proved to be a great loss to neglect the achievements of folk pedagogy, especially when it comes to raising the level of morality of schoolchildren. Two directions: cognitive and applied are carried out in the process of formation of moral and ethical concepts of education of students in extracurricular educational work, as well as in educational activities. This means that students, in addition to mastering and deepening theoretical knowledge, have opportunities for their practical application.